BRAF(V600E) protein expression and outcome from BRAF inhibitor treatment in BRAF(V600E) metastatic melanoma - Wilmott, J S (Nature Publishing Group, 2013)
BACKGROUND: To examine the association between level and patterns of baseline intra-tumoural BRAF(V600E) protein expression and clinical outcome of BRAF(V600E) melanoma patients treated with selective BRAF inhibitors. METHODS: Fifty-eight BRAF(V600E) metastatic melanoma patients treated with dabrafenib or vemurafenib on clinical trials had pre-treatment tumour BRAF(V600E) protein expression immunohistochemically (IHC) assessed using the BRAF V600E mutant-specific antibody VE1. Sections were examined for staining intensity (score 1–3) and percentage of immunoreactive tumour cells, and from this an immunoreactive score (IRS) was derived (intensity × per cent positive/10). The presence of intra-tumoural heterogeneity for BRAF(V600E) protein expression was also assessed. BRAF(V600E) expression was correlated with RECIST response, time to best response (TTBR), progression-free survival (PFS) and overall survival (OS). RESULTS: Expression was generally high (median IRS 28 (range 5–30)) and homogeneous (78%). Expression of mutated protein BRAF(V600E) as measured by intensity, per cent immunoreactive cells, or IRS did not correlate with RECIST response, TTBR, PFS or OS, including on multivariate analysis. Heterogeneity of staining was seen in 22% of cases and did not correlate with outcome. CONCLUSION: In the current study population, IHC-measured pre-treatment BRAF(V600E) protein expression does not predict response or outcome to BRAF inhibitor therapy in BRAF(V600E) metastatic melanoma patients.